2016
DOI: 10.1002/hep.28724
|View full text |Cite
|
Sign up to set email alerts
|

Liver kinase B1 regulates hepatocellular tight junction distribution and function in vivo

Abstract: Liver Kinase B1 (LKB1) and its downstream effector AMP-activated protein kinase (AMPK) play critical roles in polarity establishment by regulating membrane trafficking and energy metabolism. In collagen sandwich-cultured hepatocytes, loss of LKB1 or AMPK impaired apical ABCB11 (Bsep) trafficking, and bile canalicular formation. In the present study, we used liver-specific (Albumin-Cre) LKB1 knockout mice (LKB1−/−) to investigate the role of LKB1 in the maintenance of functional tight junction (TJ) in vivo. Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 48 publications
9
32
0
Order By: Relevance
“…More recently, Porat-Shliom et al . directly demonstrated that Lkb1 plays a key role in maintaining the functional tight junction and paracellular permeability34, which may explain why there were more EB uptake in liver tissues of Rosa-Lkb1 mice compared to control mice. These findings combined with our results indicated that the lethality of Rosa-Lkb1 mice maybe mainly due to the ablation of Lkb1 in liver or haematopoietic stem cells.…”
Section: Discussionmentioning
confidence: 97%
“…More recently, Porat-Shliom et al . directly demonstrated that Lkb1 plays a key role in maintaining the functional tight junction and paracellular permeability34, which may explain why there were more EB uptake in liver tissues of Rosa-Lkb1 mice compared to control mice. These findings combined with our results indicated that the lethality of Rosa-Lkb1 mice maybe mainly due to the ablation of Lkb1 in liver or haematopoietic stem cells.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to humans, in rodents BSIF contributes substantially to the total bile flow (Boyer, 2013;Erlinger, 1996). Therefore, to derive an estimate of apical bile secretion and bile velocity in the bile canaliculi network, we performed IVM of the well-established fluorescent tracer 6-carboxyfluorescein diacetate (CFDA) (Babbey et al, 2012;Breeuwer et al, 1995;Liu et al, 2007;Porat-Shliom et al, 2016). CFDA secretion depends on the apical multidrug resistance-associated protein 2 (MRP2) (Zamek-Gliszczynski et al, 2003), which primarily transports organic anions (BSIF) (Paulusma et al, 1999;Wielandt et al, 1999) and only to a minor extent glucuronidated bile acids (BSDF) (Akita et al, 2001).…”
Section: Intravital Imaging Of the Bile Tracer Cfda Reveals Heterogenmentioning
confidence: 99%
“…70 Interestingly, in LKB1-KO mice the level of phosphorylated AMPK is highly reduced, and CGN junctional accumulation in hepatocytes is lost, correlating with changes in cell morphology, and TJ integrity and permeability. 71 This suggests that the LKB1-AMPK kinase axis controls the apical accumulation of cingulin through its phosphorylation.…”
Section: Regulation Of Mts Organization By Junctional Proteinsmentioning
confidence: 99%